Learning Gap Assessment in Integrated Mathematics 9 - Arpilleda, Alcher J.; Resullar, Milagrosa P.; Budejas, Reubenjoy P.; Degorio, Ana Lea G.; Gulle, Reggienan T.; Somera, Mark Clinton J. (Brillo Journal, 2023)
The pandemic has profoundly impacted education, posing unprecedented challenges that demand immediate attention. Thus, this study was conducted to identify intervention activities that may be introduced on the learning gaps in Integrated Mathematics 9 for the First Quarter of the School Year 2022-2023. A quantitative quasi-experimental research using a pretest-posttest design was employed in this study and conducted on the 31 Grade 9 students of St. Paul University Surigao during the First Quarter of the School Year 2022-2023. A validated test was used to conduct the pretest and posttest to assess the learning gaps in Mathematics 9. Frequency, percentage distribution, and paired t-test were used in analyzing the data gathered. This study found that there are least-mastered competencies in the First Quarter of Mathematics 9. In addition, there is a significant difference in the pre-and posttest performance of the learners, especially after giving intervention activities such as drill, practice exercises, tutoring sessions, or small group instruction, peer tutoring and collaborative learning, expanded opportunity, explicit and technology-assisted instruction. Thus, the intervention improved learner performance and addressed least-mastered competencies. It is recommended for mathematics teachers to design further intervention materials targeting other least-learned competencies.